Mixes for Concrete Residues Removal from Sidewalk Tiles Production Molds Invention and Analysis - Onyshchenko, Volodymyr; Storozhenko, Dmytro; Senenko, Nataliia; Bunyakina, Nataliia (International Journal of Engineering and Technology, 2018)
One of the technological operations of production of sidewalk tiles, which increases cost, is removal of of hardened cement-concrete mixture residues. This mixture solidifies on any surfaces. It is easy to remove the fresh residue of the solution, but the solidified mixture is removed badly and is dangerous for both the equipment and for the template forms. In addition, the form with the remnants of hardened concrete cannot be used in the future. The task of removing concrete remnants is complicated by the fact that the concrete is of mineral nature. This means that you can remove it only with acid. Concentrated acid gives the desired effect. It penetrates into the deep layers of the dried cement mortar and destroys it. Any tool to remove concrete contains concentrated acid, which destroys the structure of concrete; Â inhibitors that protect the surface from the action of acids other auxiliary Ingredients.The means for dissolving cement mortar from the surface of the mold for production of paving slabs were created and offered. A series of experimental studies on the detection of their dissolution efficiency of hardened cement mortar were performed. A comparative analysis of the created solutions is conducted with those market analogues used in the production and have a satisfactory washing ability, but it is extremely expensive, which significantly increases the cost of the tile fulfilled. It is proved that the washing ability of new solutions meets the requirements and does not destroy the surface of the form. Methods of means preparing is simple and norequires the use of precursors. Significantly lower cost is the main advantage of created means.Â